APLIKASI PENGELOLAAN DATA OBAT DAN ALAT KONTRASEPSI BERBASIS WEB DI DINAS PPKBP3A KOTA GORONTALO - Mohidin, Ismail KH; Hermawanto, Fajar; Kantu, Nuranisa Fitriyani (Jurnal Technopreneur (JTech), 2025)
The rapid population growth in Indonesia can have negative impacts, including poverty. To address this, the government implements the Family Planning Program (KB), which in Gorontalo City is managed by the Population Control, Family Planning, Women's Empowerment, and Child Protection Office (DPPKBP3A). Effective management of contraceptives is essential for the success of this program. With technological advancements, an efficient system is needed to record contraceptive stock, usage, and expiration, and to generate reports for the office leadership. The goal of this research is to develop a web-based application using PHP, MySQL, and CodeIgniter to streamline the management and reporting of contraceptive supplies.